Kritik Representasi Masyarakat Marginal dalam Lagu Falasteen Biladi Karya Humood Al-Khudher Perspektif Poskolonial - Azis, Rifa Salma; Bakar, Irfan Abu; Rokhim, Minatur; Fazillah, Nadya Nasywah; Maulida, Silmi (Study Program of Arabic Language Teaching, 2026)
This study examines the critique of the representation of marginalized communities in the lyrics of Humood al-Khudher's song